2011
DOI: 10.1186/1743-422x-8-13
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus NS1 gene mutations F103L and M106I increase replication and virulence

Abstract: BackgroundTo understand the evolutionary steps required for a virus to become virulent in a new host, a human influenza A virus (IAV), A/Hong Kong/1/68(H3N2) (HK-wt), was adapted to increased virulence in the mouse. Among eleven mutations selected in the NS1 gene, two mutations F103L and M106I had been previously detected in the highly virulent human H5N1 isolate, A/HK/156/97, suggesting a role for these mutations in virulence in mice and humans.ResultsTo determine the selective advantage of these mutations, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 47 publications
3
69
0
Order By: Relevance
“…Previous studies have demonstrated that highly pathogenic avian influenza virus H5N1 replicated more efficiently than human influenza viruses due to its PA, PB1, and PB2 [33-35]. Our results also proved that A/tree sparrow/Henan/1/04(H5N1) was consistent with other H5N1 strains and that it rapidly and efficiently amplified in mammalian cells, which resulted in the rapid activation of IFN-β signaling in early infection.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have demonstrated that highly pathogenic avian influenza virus H5N1 replicated more efficiently than human influenza viruses due to its PA, PB1, and PB2 [33-35]. Our results also proved that A/tree sparrow/Henan/1/04(H5N1) was consistent with other H5N1 strains and that it rapidly and efficiently amplified in mammalian cells, which resulted in the rapid activation of IFN-β signaling in early infection.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, Egyptian strains exhibited no substitutions at position 92, which is related to virulence of H5N1 and cytokine resistance when changed to E [45]. F103L and M106I amino acid substitutions, which are known to be genetic determinants of pathogenicity and virulence in both human and avian hosts, were not observed in NS1 [12]. Phylogenetic analysis of NS genes showed that the Egyptian H9N2 isolates are highly homogenous and cluster together with Israeli isolates in group B, which are closely related to an H7N3 virus isolated from Pakistan in 2004 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two viral proteins, NS1 and NS2, are translated from the NS gene. Leucine at aa 103 and isoleucine at aa 106 of the NS1 amino acid sequence enhance the replication ability of viruses in vitro and in vivo and mortality in vivo (7). Their substitution expanded viral tropism in the lungs and increased the extent of infection.…”
Section: Discussionmentioning
confidence: 99%